POTENTIAL OF MEDIUM TO LONG-TERM FASTING TO TRIGGER AN AUTOIMMUNE RESPONSE THROUGH HYPERAGGRESSIVE AUTOPHAGY - Saxena, Ritwik Raj; Saxena, Ritcha (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2023)
Intermittent fasting is a lifestyle intervention that is increasingly gaining traction among the general population. An enhancement in the rate of autophagy is one of the fundamental results of intermittent fasting. Autophagy is a principal intracellular strategy for the maintenance of cellular, somatic, and systemic homeostasis. Gene-based and pharmacological therapeutic modalities which serve to dysregulate autophagy stimulate or exacerbate various diseases in a multiplicity of studies. Consistently, mutations in autophagy-related genetic processes may cause severe human pathologies. We review research and experimental models in order to establish a linkage between autophagy dysfunction to the pathogenesis of some major human disorders, particularly autoimmune disease.